Pengelolaan Parkir Di Tepi Jalan Umum Dalam Wilayah Kota Meulaboh Oleh Dinas Perhubungan Aceh Barat - Mawardani. AN Mawardani. AN; Cut Devi Maulidasari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
The increasing population in Indonesia makes the number of means of transportation used by the community also increases, cousing the flow of vehicles on the highway to increase. The purpose of this study is to see the importance of the role of the Dishub of West Aceh Regency in managing parking on the edge of public roads so that it can bee seen whether the role of Dishub can increase PAD in the city of Meulaboh. This research was conducted through a descriptive approach. The use of data collection techniques is done by means of interviews, observation, and documentation. The results show that the role of Dishub has not been able to increase the community’s PAD. The strategy that can be done is that Dishub needs to manage and supervise the formation of 8 regional points in the City of Meulaboh to manage parking on the edge of the public in collaboration with 62 parking attendants for the Meulaboh community. In addition, facilities and infrastructure are proposed as a form af providing facilities for parking attendants, namely parking clothes/vests, name bests, and parking facilities.